Risk of symptomatic dengue for foreign visitors to the 2014 FIFA World Cup in Brazil - Eduardo Massad; Annelies Wilder-Smith; Raphael Ximenes; Marcos Amaku; Luis Fernandez Lopez; Francisco Antonio Bezerra Coutinho; Giovanini Evelim Coelho; Jarbas Barbosa da Silva Jr; Claudio José Struchiner; Marcelo Nascimento Burattini (Memorias do Instituto Oswaldo Cruz, 2014)
Brazil will host the FIFA World Cup™, the biggest single-event competition in the world, from June 12-July 13 2014 in 12 cities. This event will draw an estimated 600,000 international visitors. Brazil is endemic for dengue. Hence, attendees of the 2014 event are theoretically at risk for dengue. We calculated the risk of dengue acquisition to non-immune international travellers to Brazil, depending on the football match schedules, considering locations and dates of such matches for June and July 2014. We estimated the average per-capita risk and expected number of dengue cases for each host-city and each game schedule chosen based on reported dengue cases to the Brazilian Ministry of Health for the period between 2010-2013. On the average, the expected number of cases among the 600,000 foreigner tourists during the World Cup is 33, varying from 3-59. Such risk estimates will not only benefit individual travellers for adequate pre-travel preparations, but also provide valuable information for public health professionals and policy makers worldwide. Furthermore, estimates of dengue cases in international travellers during the World Cup can help to anticipate the theoretical risk for exportation of dengue into currently non-infected areas.